The Effectiveness of Using Macbox Media to Improve Students’Grammar Mastery - Lukluan Mansuro; Muh Shofiyuddin (LPPM Universitas PGRI Semarang, 2024)
Grammar as essential aspect of English component helps students to recognize pattern and avoid errors. Alternative media is needed to make grammar learning more successful since students find it challenging to master grammar when it is taught using conventional method. This research aimed to find out about how effectively Macbox media works to help students in improving their grammar mastery. True-experimental research design was used in this research by using class X MA Matholi'ul Huda Bugel students as the research population. The two classes used as sample are 36 students of XG as the experimental class and 38 students of XH as the control class. Both classes received pre-test, treatment and post-test in order to gather research data. Then, SPSS 25.0 was utilized to examine the data outcomes. The findings of the research showed that the differences were seen in the two classes' average scores. For pre-test, the experimental class's average pre-test score was 48.47, while the control class' was 48.02. For post-test, the experimental class’s average score was 75,41 and the control class’ was 62,76. The significance value for both classes was revealed by the independent sample t-test analysis result, which were 0.000 (sig (2-tailed) < 0,05). It means that there are the significant differences between both classes. The result and discussion show the use of Macbox media is significantly effective in improving students’ grammar mastery. It means that the use of Macbox media is more effective in improving students' grammar mastery compared to the use of conventional learning method